PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 15 TAKENGON - Sinta Mahara; Alfi Syahrin; Ezmar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the application of the Problem Based Learning (PBL) method on the exposition text writing skills of tenth-grade students at SMA . the primary issue underlying this study is the students' lack of understanding regarding the structure and characteristics of exposition texts, as well as a lack of writing practice due to minimal constructive feedback. The research methodology employed is a quantitative approach with an experimental design. The research sample was determined using a cluster random sampling technique, resulting in class X1 as the experimental group (PBL method) and class X3 as the conventional group (lecture method), with each class consisting of 20 students. The data collection instrument consisted of a validated 20-item multiple-choice test and observations of teacher and student activities. The results showed that the average post-test score for the experimental class 86.75 was higher than that of the conventional class 77.25. Hypothesis testing using a t-test yielded t count 13.87 > t table 2.02 at a significance level of 0.05, leading to the rejection of H0 and the acceptance of Ha This indicates a significant difference in exposition text writing skills between the two classes. The study concludes that the application of the PBL model is more effective in improving exposition text writing skills and encouraging students to be more active compared to conventional methods